PROPOSING A HOLISTIC BASIN-SCALE AS A STRATEGY OF SMART PLANNING IN ADAPTATION TO CLIMATE CHANGE - Hamamcioglu, Cenk; Yenen, Zekiye (WIT PRESS, 2018)
Forthcoming expected results due to the phenomenon of global warming require adaptation strategies and precautions promptly to be taken on international, national and local scales. With reference to this urgent circumstance, policy frameworks executed by the international organizations, governments and ministries of nations on the consequences of adaptation to climate change have been on the agenda over the last decade. This study is derived from Turkey's policy of approach that excludes the investments of infrastructure and economic sectors from the scope of the National Climate Change Adaptation Strategy and Action Plan (2011) as a critic from the perspective of balanced development that is also an instrument of sustainability. Therefore, to clarify this deficiency, factors of infrastructure and economic sectors exacerbating the process of climate change and their mutual interaction with other sectors and nature is identified and discussed over remarkable samples from three geographically and socio-economically different basins in Turkey, studied since 2005 by the researchers of this paper. In order to coordinate adaptation to climate change, this study designates: (1) the essential role of water-soil-vegetation integrity of the life cycle with human activities, (2) controllable and observable scale for the management of risks and hazardous events, (3) opportunity to determine capacities and thresholds based on cross-sector interaction in terms of the characteristics of the local natural environment and (4) co-existence of communities and settlement system patterns sharing a fate of union of particular bases for implementing holistic basin-scale as a strategy of smart planning. As a result, compelling impacts of climate change once again verify and remind us of the significance of interdisciplinary and holistic political decision-making and modules that should involve all sectors in the strategy of smart planning for the future.
Keywords: climate change; basin scale; strategy of smart planning; CENSUS-DATA; LEVEL; VULNERABILITY; Science & Technology - Other Topics; Environmental Sciences & Ecology; Public Administration